Temperature Modulates the Effects of Ocean Acidification on Intestinal Ion Transport in Atlantic Cod, Gadus morhua - Hu, Marian Y.; Michael, Katharina; Kreiss, Cornelia M.; Stumpp, Meike; Dupont, Sam; Tseng, Yung-Che; Lucassen, Magnus (Frontiers in Physiology, 2016)
CO2-driven seawater acidification has been demonstrated to enhance intestinal bicarbonate secretion rates in teleosts, leading to an increased release of CaCO3 under simulated ocean acidification scenarios. In this study, we investigated if increasing CO2 levels stimulate the intestinal acid–base regulatory machinery of Atlantic cod (Gadus morhua) and whether temperatures at the upper limit of thermal tolerance stimulate or counteract ion regulatory capacities. Juvenile G. morhua were acclimated for four weeks to three CO2 levels (550, 1,200 and 2,200 μatm) covering present and near-future natural variability, at optimum (10°C) and summer maximum temperature (18°C), respectively. Immunohistochemical analyses revealed the subcellular localization of ion transporters, including Na+/K+-ATPase (NKA), Na+/H+-exchanger 3 (NHE3), Na+/HCO3- cotransporter (NBC1), pendrin-like Cl-/HCO3- exchanger (SLC26a6), V-type H+-ATPase subunit a (VHA) and Cl- channel 3 (CLC3) in epithelial cells of the anterior intestine. At 10°C, proteins and mRNA were generally up-regulated for most transporters in the intestinal epithelium after acclimation to higher CO2 levels. This supports recent findings demonstrating increased intestinal HCO3- secretion rates in response to CO2 induced seawater acidification. At 18°C, mRNA expression and protein concentrations of most ion transporters remained unchanged or were even decreased, suggesting thermal compensation. This response may be energetically favorable to retain blood HCO3- levels to stabilize pHe, but may negatively affect intestinal salt and water resorption of marine teleosts in future oceans.